Characterization of Proteolytic Enzymes from Sparus aurata L. Viscera, Obtained by Supercritical Carbon Dioxide, Mechanical and n-hexane Extraction Methods - Lamas, Daniela Lorena (2015)
The oil in gilthead sea bream (Sparus aurata L.) was extracted using an environmental friendly solvent, supercritical carbon dioxide (SC-CO2) at a flow extraction process, mechanical method and n-hexane solvent extraction. The SC-CO2 extraction was carried out at temperature 45 °C and 25 MPa of pressure. The flow rate of CO2 (10Kg/h) was constant at the entire extraction period of 240 min. The extracted residue after oil extraction was used for activity measurement of digestive enzymes. In addition, an untreated viscera crude portion was used as a control. Crude protein extract exhibited its maximal activity at pH 8 and 60ºC of temperature using azocaseín as a substrate. Results relative to the substrate specific BAPNA, indicated that a protease recovery was a trypsin type enzyme. All methods achieved higher activity than crude extract. The supercritical fluid extraction was found to be the best for the partial purification of protein phase and retains the highest proteolytic activity. Mechanical extraction was found to be the slightest protein recovery method. Stability results obtained have shown the great potential of these specific compounds for use as nutraceuticals or as ingredients for functional foods. In addition, the stability against surfactants suggests that this enzyme can be incorporated as an ingredient in detergent formulations.